Therapeutic potential of Piper aduncum leaf extract in the control of monogeneans in tambaqui (Colossoma macropomum) - Affonso, Elizabeth Gusmão; Ono, Eduardo Akifumi; Pohlit, Adrian Martin; Torres, Zelina Estevam dos Santos; Queiroz, Marieta Nascimento de (Aquaculture, 2022)
Piper aduncum is a native plant that of the Amazon with important medicinal properties and is a sustainable source of raw material for the pharmaceutical industry. The ethanol extract of this plant was evaluated for its ability to control monogeneans of Colossoma macropomum, using in vitro and in vivo tests, lethal concentration (LC50–24h) determination. Phytochemical screening and an in vitro test were performed, and the substance was found effective in both analyses. Testing using various doses revealed the lethal concentration (LC50–24h) of the ethanol extract in tambaqui as 79 mg L−1. The in vivo test, using two baths, with a basal bath (without parasites and treatment), two controls (water and water with methanol), and 40 and 60 mg L−1 of extract, demonstrated effectiveness of 85.89 and 99.21%, respectively. An increase in hematocrit (Ht) and hemoglobin ([Hb]) was observed in the treatments compared to the two controls, along with hyperglycemia, and increases in plasma cortisol by 60 mg L−1. The results suggest that 60 mg L−1 of the ethanol extract is effective for controlling tambaqui monogeneans, without compromising fish health and survival, indicating its anthelmintic potential for the aquaculture industry. © 2022
Keywords: Aquaculture; Fish parasites